Inclusive annihilation of antiprotons on deuterium - Frederico, T.; Carlson, B. V.; Mastroleo, R. C.; Tomio, Lauro [UNESP]; Hussein, M. S. (American Physical Society (APS), 1990)
The inclusive annihilation of antiprotons on deuterium is calculated within a three-body model. At very low antiproton energies (Ep»<2.2 MeV), structure is observed in the energy spectra of emerging protons at forward angles. The theory can be easily extended to higher antiproton energies. © 1990 The American Physical Society.